Oxidation-reduction potential of UF white cheese: Impact on organic acids, volatile compounds and sensorial properties. (September 2020) - Bulat, Tugba; Topcu, Ali
Abstract: The purpose of this study was to determine the impact of extracellular oxidation-reduction (redox) potential ( E h ) on organic acids and residual lactose, volatile compounds, and sensorial properties of experimental ultrafiltered (UF) cheese during ripening. In addition, the changes in E h and pH of UF cheese were simultaneously determined during the simulated UF cheesemaking. Sodium hydrosulfite (reducing agent) and potassium iodate (oxidizing agent) were added to UF retentate to modify E h of cheeses. After addition of the redox agents, E h7 values of UF retentates (pH 6.5 ± 0.1) used in the production of control, reduced and oxidized cheeses were +330, −157 and + 340 mV, while experimental UF cheeses had E h7 values of −230, −247 and + 241 mV at 25 °C, respectively, 3 days after cheese manufacture. E h was significantly effective on the sugar metabolism of starter cultures thereby on organic acid contents. Lactose fermentation was limited in the oxidized cheeses. The most important differences between volatile compounds of the cheeses resulted from ethanol, benzaldehyde, 4-methyl benzaldehyde, and sulfurous compounds such as methanethiol, dimethyl disulfide and dimethyl trisulfide. The results indicate that redox potential is a crucial parameter that influences organic acids and volatile compounds and consequently of sensorial characteristics of cheese. Highlights: E h affected lactose metabolism of starter lactococci. E h influenced organic acid and volatile compound profiles of UF white cheese. Low E h was favored by starters to achieve suitable pH for UF white cheese. Negative E h was required to get desirable sensorial attributes for UF white cheese.